Electrophysical Properties of Epoxy Composite Materials Filled with Carbon Black Nanopowder - Andriy Buketov; Serhii Smetankin; Eduard Lysenkov; Kyrylo Yurenin; Oleksandr Akimov; Serhii Yakushchenko; Iryna Lysenkova (Advances in Materials Science and Engineering)
The effect of carbon black (CB) nanopowder on the electrical properties of polymer composite systems based on the epoxy resin is investigated using the method of impedance spectroscopy. It is established that the electrical and dielectric properties of the studied systems significantly depend on the nanofiller content. It is found that electrical conductivity and dielectric constant exhibit percolation behavior when the filler’s content increases. In this case, the electrical conductivity increases exponentially, indicating the formation of filler electrically conductive mesh inside the polymer matrix. A small jump in electrical conductivity when reaching the percolation threshold indicates the formation of indirect contacts between the particles. The value of the percolation threshold of conductivity is 8%. It is shown that the dielectric constant of epoxy nanosystems is almost unchanged in the frequency range of 102–105 Hz. It is related to the structural features of the filler particles, which ensure the existence of a minimal dielectric gradient between the matrix and the filler. It is found that the dielectric constant of the studied systems also shows percolation behavior. The obtained material based on the epoxy matrix is characterized by a high value of dielectric constant, which at a carbon black nanopowder content of 29% is 4680. This material is characterized by relative frequency invariance and a high value of dielectric constant, so it has great potential for practical application.